Derivatives of Cinnamic Acid Esters and Terpenic Diversity in Volatiles of Thirty-Six Sand Ginger (Kaempferia galanga L.) Accessions of Eastern India Revealing Quality Chemovars - Subhashree Singh; Suprava Sahoo; Bhaskar Chandra Sahoo; Manaswini Dash; Sanghamitra Nayak; Basudeba Kar (Molecules, 2022)
The essential oil of Kaempferia galanga L. commonly known as sand ginger has increased its demand in national and international market for decades. Cinnamic acid esters like ethyl-p-methoxy cinnamate (EPMC) and ethyl cinnamate (EC) are major constituents in its essential oil. In spite of the high demand for the plant as raw material, identification of quality chemovars having high essential oil (EO) yield and constituents is still at an infant stage. With this in mind, we have evaluated the EO yield of 36 accessions from three provinces of Eastern India, which varied within a range of 0.41 ± 0.01 to 2.63 ± 0.03 v/w. Further, a total of 65 compounds were detected by gas chromatography and mass spectrometry (GC-MS) with area percentages varying from 76.16 to 97.3%. EPMC was found to be the major component in 14 accessions with area percentages varying from 10.7% to 41.1%, whereas other 22 accessions showed EC as the major constituent, varying from 16% to 29.1%. Further, a diversity study among accessions was performed by agglomerative hierarchical clustering (AHC) and principal component analysis (PCA) analysis based on the abundance of identified constituents, which categorized all 36 accessions into three clusters. Thus, the present study helps to identify quality chemovar K.g16 and K.g14 with respect to oil yield and constituents, respectively, which could be used to guide commercial cultivation and further improvement of the taxa.